2000
DOI: 10.1016/s0002-9440(10)64785-2
|View full text |Cite
|
Sign up to set email alerts
|

Chromogenic in Situ Hybridization

Abstract: Determination of HER-2/neu oncogene amplification has become necessary for selection of breast cancer patients for trastuzumab (Herceptin) therapy. Fluorescence in situ hybridization (FISH) is currently regarded as a gold standard method for detecting HER-2/neu amplification, but it is not very practical for routine histopathological laboratories. We evaluated a new modification of in situ hybridization, the chromogenic in situ hybridization (CISH), which enables detection of HER-2/neu gene copies with convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 321 publications
(75 citation statements)
references
References 12 publications
1
73
0
1
Order By: Relevance
“…Evaluations were performed blinded to all clinical and biological variables. Methods for PTEN IHC, PIK3CA mutational screening, and HER2 chromogenic in situ hybridization have been described (16,38). Stathmin IHC is described in SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluations were performed blinded to all clinical and biological variables. Methods for PTEN IHC, PIK3CA mutational screening, and HER2 chromogenic in situ hybridization have been described (16,38). Stathmin IHC is described in SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…In several breast cancer studies, HER2 CISH correlated well with FISH and IHC [44, 46–51]. In gastric cancer, one study systematically analyzed the concordance between CISH and FISH assays and observed a perfect correlation in 128 samples [52].…”
Section: Human Epidermal Growth Factor Receptormentioning
confidence: 99%
“…The utility of CISH has been investigated in several studies. Tanner and colleagues [28]analyzed freshly frozen tumor samples and archival formalin-fixed paraffin-embedded tissue sections by FISH, IHC and CISH. HER2 amplification determined by FISH and CISH was comparable and in general agreement with results for HER2 receptor overexpression obtained by IHC.…”
Section: Her2 Testingmentioning
confidence: 99%